Avaliação da atividade de enzimas que degradam nucleotídeos de adenina e do perfil oxidativo em ratos com sepse induzida - Bertoncheli, Claudia de Mello (2014)
Sepsis is recognized as a systemic inflammatory response (SIRS) to infection with the presence of progressive tissue damage, where multiple organ failure is the most severe expression. The purinergic signaling plays an important role in inflammatory response modulation as well as in immune responses through its extracellular biomolecules, such as adenine nucleotides and its derivative nucleoside adenosine. These signalling molecules are released by cells in response to damage or cellular stimuli induced by pathogens. Adenine nucleotides and adenosine effects are promoted by activation of specific purinergic receptors controlled by an enzymatic cascade on cell surface. In addition to immunologic changes, oxidative stress has an important part in sepsis pathophysiology, contributing to its deleterious systemic effects such as tissue hypoxia and organ failure. This study aims to evaluate the activity of the E-NTPDase, which degrade adenine nucleotides in lymphocytes, as well as analyse the oxidative profile in brain, heart, liver and kidney in rats submitted to experimental sepsis. The sepsis was induced by cecal ligation and puncture (CLP). The evaluation of the effects of sepsis on E-NTPDase activity in lymphocytes, as well as on the oxidative stress parameters in different tissues, was divided into two stages. On the first stage, the animals were split into two groups: (1) negative controls and (2) septic, which evaluated the activity of the E-NTPDase and histological analysis of the kidneys, liver and lung. On the second stage, the animals were divided into three groups: (1) negative controls, (2) sham e (3) septic. An increase in ATP hydrolysis was observed in sepsis-induced rats when compared to the control group. Nevertheless, the E-NTPDase activity remained unchanged when ADP was applied as substrate. Histological analyses of kidneys, liver and lung have shown vascular congestion, necrosis and inflammatory mononuclear cell infiltration when compared to control group. Regarding the antioxidant activity, no difference was observed in the NPSH content and SOD activity in the organs analysed. Concerning the oxidative stress parameters, the carbonyl protein content showed no significant difference in brain and liver, whilst in heart and kidney a decrease was observed in the septic group. No significant difference in TBARS levels was observed in brain, however an increase was observed in kidney while a decrease was observed in heart and liver. E. coli was identified as the etiological agent. On the septic group, significant hematological changes such as leucocytosis and thrombocytopenia were observed. This reduction in TBARS levels in heart and liver does not agree with data on the literature; this may be due to the employment of different induction techniques among studies, added to altered neutrophil function and and also the characteristics inherent to the pathogenic microorganism. Our findings suggest that the increase in ATP hydrolysis in induced sepsis may be a dynamic response in order to eliminate the increased ATP levels resulting from cell death. Regarding the oxidative stress parameters, the reduction in heart and liver may be due differences in the sepsis induction of CLP model by between different research groups added to altered neutrophil function and and also the characteristics inherent to the pathogenic microorganism.